MANAJEMEN DAKWAH TAKMIR MASJID KAMPUS DARUNNAJAH IAIN PURWOKERTO DALAM MEMBENTUK KHARAKTERISTIK ISLAM RAHMATAN LIL’ALAMIN - Arsam Arsam (Jurnal Dakwah Tabligh, 2020)
Islam rahmatan lil'alamin which is the core of the conflict. Islam rahmatan lil'alam is still far from reality. The mercy is only at the level of the slogan, what appears on the surface is that it is dominated by violent reactions, especially in response to global issues. It seems as if Muslims have no better alternative than committing violence. Along with the times and this sophisticated technology is also used by radical groups to spread radicalism through social media which can endanger the future of the younger generation. This phenomenon is the background for the preaching of the Takmir Darunnajah Mosque IAIN Purwokerto to build the Islamic characteristics of Rahmatan lil'alamin.